Geochemical characteristics of Holocene aeolian deposits east of Qinghai Lake, China, and their paleoclimatic implications - Ding, Zhiyong; Lu, Ruijie; Lyu, Zhiqiang; Liu, Xiaokang (The Science of the total environment, 2019)
The paleoclimate evolution of the northeastern Tibetan Plateau (TP), especially in the Qinghai Lake Basin (QLB), has long been a subject of interest to scholars due to the particularity of the geographical location. However, because of the uncertainties of the chronologies and the interpretations of the proxies used, climate change in this region remains controversial during the Holocene. The Hudong dunefield is located to the east of Qinghai Lake and is the largest sand accumulation area in the QLB. In this study, deposits in the Holocene aeolian sand-paleosol sequences Chengou East (CGE) and Qinghaihu Country (QHH) in the Hudong dunefield were analyzed to determine their elemental geochemical characteristics and paleoclimatic implications. Combining the grain size, total organic carbon (TOC) and redness, we investigate the paleoclimate changes in this region and its response to the East Asian Summer Monsoon (EASM) during the Holocene. The high Na2O/Al2O3 ratios and low chemical index of alteration (CIA) values suggest that most of the sediments are unweathered to weakly weathered, although some mid-Holocene samples are moderately weathered. The multiproxy analysis indicates that the local climate was broadly coincident with that of the northeastern TP and most regions of northern China, implying that the paleoclimate of the QLB was closely related with the evolution of the EASM during the Holocene. Additionally, after the 9.2 ka BP cold event, the chemical weathering increased gradually. The higher CIA and TOC contents and lower redness and mean grain size from 8.7 to 4.0 ka BP are possibly associated with the mid-Holocene optimum period and indicate intensified chemical weathering, denser vegetation cover and weakened aeolian activity in the QLB in response to a warmer and more humid climate. After 4.0 ka BP, the lower degrees of chemical weathering indicate that the study area was dominated by a relatively cold and dry climate, and several alternating warm-wet and cold-dry intervals occurred from 3.1 to 0.6 ka BP. [Display omitted] •Qinghai Lake Basin was dominated by the primary weathering during the Holocene.•An intensified chemistry weathering during the mid-Holocene•The local climatic change is correlated with the East Asian Summer Monsoon.•A multiproxy approach is key for reliable paleoclimatic interpretation.